2017
DOI: 10.1590/0074-02760160360
|View full text |Cite
|
Sign up to set email alerts
|

Stable expression of Mycobacterium bovis antigen 85B in auxotrophic M. bovis bacillus Calmette-Guérin

Abstract: BACKGROUND Bovine tuberculosis (TB) is a zoonotic disease caused by Mycobacterium bovis, responsible for causing major losses in livestock. A cost effective alternative to control the disease could be herd vaccination. The bacillus Calmette-Guérin (BCG) vaccine has a limited efficacy against bovine TB, but can improved by over-expression of protective antigens. The M. bovis antigen 85B demonstrates ability to induce protective immune response against bovine TB in animal models. However, current systems for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Linalool and E-nerolidol were reported as the major constituents of its essential oil [29,30], whereas a recent study revealed that the composition was variable and only E-nerolidol was detected as a common constituent among the eight cultivars from different places in Guatemala [31]. Although linalool has been reported to show anti-trypanosomal activity [32], nothing has been reported on anti-trypanosomal constituents of the MeOH extract of this species. Aerial parts of P. jaquemontianum (510 g) were extracted with MeOH at room temperature to give 83.5 g of the extract.…”
Section: Resultsmentioning
confidence: 97%
“…Linalool and E-nerolidol were reported as the major constituents of its essential oil [29,30], whereas a recent study revealed that the composition was variable and only E-nerolidol was detected as a common constituent among the eight cultivars from different places in Guatemala [31]. Although linalool has been reported to show anti-trypanosomal activity [32], nothing has been reported on anti-trypanosomal constituents of the MeOH extract of this species. Aerial parts of P. jaquemontianum (510 g) were extracted with MeOH at room temperature to give 83.5 g of the extract.…”
Section: Resultsmentioning
confidence: 97%
“…BCG is the currently available vaccine against TB. It expresses an Mtb immunodominant protein Antigen 85B (Ag85B) [ 23 ]. The antigen85 (Ag85) proteins comprise of Ag85A, Ag85B, and Ag85C.…”
Section: Discussionmentioning
confidence: 99%
“…(12,25) On the other hand, the level of expression of heterologous genes in mycobacteria is modulated mainly by the promoter, yet not solely. Although, there are several studies performed with a set of promoters and in different vectors as backbone, (20,26) investigations in the search for new and improved promoters continue to be performed. (25,27) We have extensive experience with the mycobacterial expression vector pLA71, containing the P BlaF* promoter, which we have used to express many different antigens from different pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…(6) On the other hand, it has been shown that maintaining the plasmid based on antibiotic resistance does not determine that the antigen will be expressed over time. (20) Rizze et al (20) developed an auxotrophic mycobacterial system based on leuD complementation to express 85B and 85BT antigens (BCG ΔleuD-85B and BCG ΔleuD-85BT), which proved to be stable both for the presence of the plasmid and for the expression of these antigens over a long period of time after immunisation of mice. We have previously obtained a BCG strain auxotrophic for lysine, (BCG-Δ-lysA), complemented with a pLA71-based expression vector (7) which was shown to maintain expression of the antigen through several in vitro passages without antibiotic selection (results not shown).…”
mentioning
confidence: 99%